Reconstruction of Holocene hydroclimatic variability in subarctic treeline lakes using lake sediment grain-size end-members. (June 2018) - Macumber, Andrew L; Patterson, R Timothy; Galloway, Jennifer M; Falck, Hendrik; Swindles, Graeme T
Current climate trends are expected to result in the northward expansion of the subarctic treeline leading to changes in vegetation cover and permafrost distribution, as they did during the Holocene Climate Optimum when the treeline was 150 km north of its current position. The impacts of these changes on the region's hydrology are still poorly understood. The grain-size distributions of treeline lake sediments provide an important proxy related to spring melt conditions that can be used to reconstruct hydroclimatic variability. End-member mixing analysis was used to model depositional end-members in 55 modern lake sediment samples and two sediment cores spanning the mid- to late Holocene collected from above and below the treeline in the central Northwest Territories, Canada. Cold climatic intervals (e.g. 'Dark Ages Cold Period', 'Little Ice Age') were characterised by an increase in the very coarse silt and the fine sand end-members. This was interpreted to be a response to degradation of vegetation cover and/or permafrost development. We observed increases in fine and coarse silt end-members during warmer climatic intervals (e.g. Medieval Climate Anomaly) and over the past c. 300 yr BP. This pattern is probably the result of extended melt seasons, with greater losses to evaporation and increased infiltration. The most pronounced palaeo-hydroclimatological change over the past c. 8000 yr BP was the abrupt increase in a very coarse silt end-member (mode = 50–200 µm) at c. 6300 yr BP. We interpreted the sedimentological change as an increase in winter precipitation and more energetic spring melt conditions, leading to the spring melt becoming the dominant lacustrine sediment delivery mechanism. These results place modern hydrological changes in a millennial context and show that analysis of temporal changes in the hydroclimatological system can provide insight into the future states of these sensitive subarctic ecosystems.